Ecology and functions of Trichoderma in coffee and cocoa agroecosystems: bibliometric and systematic insights for sustainable agriculture - Santillan-Culquimboz, Henry W.; Leiva, Santos Triunfo; Munoz-Salas, Milagros Ninoska; Meza-Maicelo, Wagner; Lozano-Isla, Flavio; Oliva-Cruz, Manuel; Balcázar-Zumaeta, César R. (Frontiers in Microbiology, 2025)
Coffee and cacao are strategic tropical crops increasingly threatened by climate change, soil degradation, and disease outbreaks. In this context, Trichoderma has emerged as a multifunctional microorganism with significant ecological roles and biotechnological applications. This study aimed to comprehensively assess the functions of Trichoderma in coffee (Coffea spp.) and cacao (Theobroma cacao) agroecosystems using a combined bibliometric and systematic review approach. Bibliometric analyses of 266 documents indexed in Scopus and Web of Science (1985–2025) revealed sustained publication growth, with Latin America and the Asia-Pacific region as leading contributors. Six major thematic clusters were identified, encompassing biological control, plant growth promotion, biotechnology, and fungal diversity. The systematic review confirmed that Trichoderma colonizes diverse ecological niches (rhizosphere, endosphere, phyllosphere) and acts through mycoparasitism, antibiosis, nutrient solubilization, and induced systemic resistance. Evidence highlights its effectiveness against key pathogens (Moniliophthora spp., Phytophthora spp., Hemileia vastatrix) and its contribution to host growth and stress tolerance. Less explored applications include heavy-metal bioremediation, waste bioconversion, mycorrhizal interactions, and entomopathogenic potential. However, gaps remain regarding strain variability under field conditions and underexplored avenues such as cadmium remediation in cacao. Overall, the findings position Trichoderma as a cornerstone microbial resource for enhancing the resilience and sustainability of coffee and cacao agroecosystems.